Antimullerian Hormone and Impending Menopause in Late Reproductive Age: The Study of Women's Health Across the Nation. Issue 9 (September 2020) - Finkelstein, Joel S.; Lee, Hang; Karlamangla, Arun; Neer, Robert M.; Sluss, Patrick M.; Burnett-Bowie, Sherri-Ann M.; Darakananda, Karin; Donahoe, Patricia K.; Harlow, Sioban D.; Prizand, Sarah H.; Joffe, Hadine; Kumar, Ajay; et al.
Abstract : (Abstracted from J Clin Endocrinol Metab 2020;105(4):e1862–e1871) Follicle-stimulating hormone (FSH) is a widely used biomarker of ovarian age and indirectly of ovarian reserve; however, it has significant limitations. Antimullerian hormone (AMH) provides a more direct index of ovarian activity and remains at a stable level throughout the menstrual cycle, unlike FSH, allowing measurement at any time without affecting interpretation.